'The ghosts of menin gate': Art, architecture and commemoration - Stephens, John (Sage Publications, 2009)
© 2009 SAGE Publications, Los Angeles.Straddling the Meensestraat through the old ramparts of Ypres in Belgium is the Menin Gate. Designed by the architect Reginald Blomfield in 1922, this building commemorates the 56,000 British Empire missing from the battles of the Ypres Salient during the first world war. This solemn memorial has significance and commemorative meaning to relatives of those whose names appeared on the structure. Responding to an eerie vision at the Gate in 1927, the Australian artist and soldier William Longstaff painted his allegorical work Menin Gate at Midnight , showing it as an ethereal structure in a brooding landscape populated with countless ghostly soldiers. The painting was an instant success and was reverentially exhibited at all Australian capital cities. This article contends that both gate and painting-in diverse and complementary ways-attempt to come to terms with the idea of the missing as a special class of soldier death and to create particular sites of memory for those who had no physical remains over which to grieve.